2020
DOI: 10.1007/s13738-020-02049-z
|View full text |Cite
|
Sign up to set email alerts
|

The ACE2 as a “rescue protein” or “suspect enzyme” in COVID-19: possible application of the “engineered inactive hrsACE2” as a safer therapeutic agent in the treatment of SARS-CoV-2 infection

Abstract: COVID-19 is a devastating global pandemic around the world. While the majority of infected cases appear mild, in some cases, individuals present respiratory complications with possible serious lung damage. There are no specific treatments for COVID-19 as yet. Many repurposed antiviral drugs have had disappointing outcomes. Angiotensin-converting enzyme 2 (ACE2), an enzyme that physiologically counters renin–angiotensin–aldosterone system activation, functions as a receptor for both SARS viruses. The current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 66 publications
2
7
0
Order By: Relevance
“…Collectively, data suggested that the beneficial effects of APN01 can include slowing down the viral entry, spread and ultimately viral neutralization. It can also preserve cellular ACE-2, hence maintaining its protective activity to vital body organs [ 8 , 56 , 115 , 119 ].…”
Section: Potential Sars-cov-2 S Protein-based Therapiesmentioning
confidence: 99%
“…Collectively, data suggested that the beneficial effects of APN01 can include slowing down the viral entry, spread and ultimately viral neutralization. It can also preserve cellular ACE-2, hence maintaining its protective activity to vital body organs [ 8 , 56 , 115 , 119 ].…”
Section: Potential Sars-cov-2 S Protein-based Therapiesmentioning
confidence: 99%
“…Since ACE2 inhibitors and Ang II AT1 receptor antagonists have the potential to increase ACE2 expression, which may aggravate COVID-19, we recommend critical publications regarding the use of renin-angiotensin inhibitors and COVID-19 ( Bavishi et al, 2020 ; Peiró and Moncada, 2020 ; Sanchis-Gomar et al, 2020 ; Sommerstein et al, 2020 ; Vaduganathaan et al, 2020 ). Yet the presence of the soluble and active isoform of ACE2 may be beneficial in COVID-19 patients since soluble ACE2 may compete with the membrane enzyme, limiting its role as a SARS-CoV-2 receptor, and decreasing the Ang II plasma levels ( Khodarahmi et al, 2021 ). As a therapeutic target, the restoration of ACE2 through the administration of recombinant ACE2 may reverse the lung-injury process ( Monteil et al, 2020 , 2021 ; Siriwattananon et al, 2021 ; Zhang et al, 2021 ).…”
Section: Angiotensin-converting Enzyme 2 and The Implication Of The R...mentioning
confidence: 99%
“…On the other hand, SARS‐CoV‐2 downregulates ACE2 and reduces Ang (1–7) after infection. As a result, the high severity and high mortality rate among these patients could be due to reasons, such as vasoconstriction, vascular damage, fibrosis, proliferation, and inflammation due to reduction of Ang (1–7) 3 …”
Section: Introductionmentioning
confidence: 99%
“…1 Ang (1-7) exerts vasodilation, vascular protection, anti-fibrosis, antiproliferation, and anti-inflammation actions. The heart, brain, and kidney are major sources to produce Ang (1)(2)(3)(4)(5)(6)(7). This peptide as a vasodilator agent plays an important role in improving heart and lung functions.…”
mentioning
confidence: 99%
See 1 more Smart Citation